Peran komunitas bale ceria lanji dalam membina karakter gotong royong remaja - M. Zainul Farhan; Lalu Sumardi; Humamurrizqi Humamurrizqi (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study examines the role of the Bale Ceria Lanji Community in fostering the gotong royong (mutual cooperation) character among adolescents in Darmaji Village, Kopang District. Using a qualitative ethnographic approach, data were collected through semi-structured interviews, participatory observation, and documentation, with validity ensured through triangulation. The findings reveal two main dimensions of the community's role. First, program implementation includes literacy activities (group reading, book discussions, art classes), youth involvement as facilitators and community mobilizers, and environmental and social service activities. Second, the internalization of gotong royong values is carried out through modeling, mentoring, monitoring, mediating, and positive reinforcement for active youth participation. Supporting factors include the commitment of community organizers, support from parents and the broader community, the Sasak cultural tradition of mutual cooperation as social capital, engaging and creative program designs, and institutional support from the Village Government. Conversely, inhibiting factors include limited operational funding, the distraction of digital technology and social media, inconsistent member attendance, and insufficient leadership regeneration.